‎ Nilai Kasih Sayang Rasulullah dalam Ceramah Ustadz Adi Hidayat - Alya Rahmah; Desy Nursyawaliya; Ali Machmud Badarudin; Muhammad Afiq Azri; Muhammad Yusup Nst; Ibnu Rozali (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
Islamic teachings encourage every believer to always love and emulate the Prophet Muhammad (peace be upon him). This study aims to explore and explain Ustadz Adi Hidayat's sermon on the depth of the Prophet Muhammad's love and longing for his followers, which was presented via the YouTube platform. The study method used was descriptive qualitative, by listening to the sermon live, noting important points, and then analyzing its contents. The findings of this study indicate that the Prophet's love and longing can be seen from various aspects, such as the Prophet's deep longing for his followers in the end times (those of us who are living now), the Prophet's concern for the difficulties we face, and the intercession he will provide on the Day of Judgment. Ustadz Adi Hidayat explained that even though we have never met, the Prophet's love and longing for us is very real. He even specifically saved the most efficacious prayers to help his followers in the afterlife. Therefore, it is crucial for Muslims to always remember the Prophet Muhammad's love and longing and to reciprocate it by actively reciting blessings and implementing his good behavior in their daily lives.